PENGARUH PROFITABILITAS, LEVERAGE DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PROPERTI, REAL ESTATE DAN KONSTRUKSI BANGUNAN - Yanti, Putu Diah Melinda; Abundanti, Nyoman (E-Jurnal Manajemen, 2019)
This study was conducted to examine the effect of profitability, leverage and dividend policy on the value of companies in property, real estate and building construction companies on the Indonesia Stock Exchange which distributed dividends in a period between 2014 and 2017. Thirteen samples were examined. (13) companies selected through purposive sampling method that determines certain criteria in determining samples to be used in the observation period for four years. The data collection method used in this study is a nonparticipant observation method, namely by observing the company's financial statements. Data analysis was done by multiple linear regression analysis techniques. Based on the results of the analysis it was found that profitability and leverage had a significant positive effect on firm value, while dividend policy had a negative and insignificant effect. This indicates that dividend policy is not one of the main factors affecting the value of the company. Keywords: company value, dividend, profitability, leverage